Pelatihan Perhitungan Pajak Orang Pribadi Di Smk Yatindo Kota Bekasi - Iren Meita; Dade Nurdiniah; Indra Wijaya; Ferisanti (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
SMK Yatindo is located in Mustika Jaya which focuses on Accounting, Management education. The obstacles faced are the lack of introduction and knowledge of personal income tax calculations and the difficulty in presenting material related to personal income tax to students. The form of solution is based on a mutual agreement with SMK Yatindo, the socialization of taxes given from an early age is important so that it should be done regularly and not just for a moment. The method used in this training is a service learning method approach through three stages, namely preparation, training and evaluation. To measure the achievement of training using descriptive qualitative and data collection techniques are done by giving questionnaires and questions and answers by conducting pre tests and post tests. The results of this training showed an increase in knowledge by students and students of SMK Yatindo where they were able to answer correctly the Post test questions, which in its implementation was 70%, as well as the level of partner satisfaction of 89.7% stated that they were very satisfied with this training, and students hoped that training could be carried out regularly.